The end of all skies - Sales, Vincent C. (USA Penguin Books, an imprint of Penguin Random House, 2022)
"The final days of Sun Girna Ginar have arrived. The old witch in the marketplace knows it, but no one believes her. How could the Sultanate fall when the God-Sultan rules over the earth and Skyworld? How could anyone ever defeat General Marandang, the giant slayer, and the city's champion, Lam-Ang? Entering into a wager with the gods, the old witch promises to destroy the city. And by granting the most insignificant the ability to make their dreams come true, it all comes to pass. We witness the fall of the Sultan's great city through their stories: the hunter who seeks revenge, the one-handed thief who wants justice, and the exiled datu searching for redemption. Together, they bring about the destruction of the city of Sun Girna Ginar. Its walls are breached by the six-headed giant of Gawi-Gawen as fire consumes the Palace and the never-ending rain swallows the city in flood. The End of All Skies is a story of reclaimed myths, but it is also a mirror of recent history, of today. It revisits our lost past and entreats us to never forget the sins committed against us, while reminding us of the power and humanity each of us possesses."--Back cover
In English.
Keywords: Short stories, Philippine (English); Fantasy fiction, Philippine (English); Philippine fiction (English)